Fish Diversity and Water Quality Parameters of Mechi River, Jhapa, Province No. 1, Nepal - ADHIKARI, ASHIM; LIMBU, JASH HANG; PATHAK, SOMIKA (Borneo Journal of Resource Science and Technology, 2021)
Species diversity is widely recognised as an important trait of functioning and resilient ecosystem. Spatio-temporal patterns of fish community structure in the Mechi River was studied based on stratified random survey, conducted between September 2018 and April 2019. The survey was conducted at three different sampling stations in three different seasons. For the fish sampling, two cast nets of different sizes were used, one having large mesh size of 0.5 cm, 3 m diameter and 2 kg weight and another having mesh size of 2 cm, 6 m diameter and 6 kg weight. In addition, drag net and gill net were also used to collect the fish samples. A total of 1,772 fishes belonging to 4 orders, 8 families, 16 genera and 33 species were documented. The results from the similarity percentage analysis indicated that, the species Schistura devdevi, Brachydanio rerio, Puntius sophore, Barilius barila, Schistura beveani and Puntius terio were the most copious fish species recorded from the Mechi River. One-way analysis of similarity testing for space and time variations in fish community indicated that there was a significant difference in space (R = 0.66, p<0.01) but no significant difference in time (R = -0.0123, p>0.433). The Canonical Correspondence Analysis hinted that dissolved oxygen, water velocity and pH have shown to influence the fish assemblage structure in Mechi River.